High-strength nano-composite stiffening filling master batch and preparation method thereof

By using nanofillers such as nanodiamond, nanosilicon carbide and bio-based nanocellulose in the filling masterbatch, combining matrix materials such as polyimide, polyether etherketone and bio-based polylactic acid, and pretreatment of nanofillers, dispersion and coating of matrix materials, a high-strength nanocomposite rigid-filled masterbatch is formed, which solves the problems of poor dispersion and mechanical properties damage in traditional filling masterbatches, and achieves higher mechanical properties and biocompatibility.

CN119684794AInactive Publication Date: 2025-03-25南通瑞隆新材料有限公司

Patent Information

Application Number
CN202510022966.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The problems of poor dispersion of fillers, damage to mechanical properties, insufficient hardness and poor interface bonding in traditional filling masterbatches.

Method used

Nanodiamond, nanosilicon carbide and bio-based nanocellulose are used as nanofillers, combined with polyimide, polyether etherketone and bio-based polylactic acid as matrix materials, and a variety of functional additives are added. Through the pretreatment and dispersion of nanofillers, preparation and coating of matrix material solution, molding, curing and post-treatment, etc., a high-strength nanocomposite rigid-filled masterbatch is formed.

Benefits of technology

The rigidity and strength of the filling masterbatch are significantly improved, their mechanical properties and biocompatibility are enhanced, and the problems of poor dispersion, damage to the mechanical properties, insufficient hardness and poor interface bonding of traditional filler masterbatches are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-strength nano composite stiffening filling master batch and a preparation method thereof, and relates to the technical field of high polymer materials, the raw materials comprise a nano filler, a matrix material and a functional additive; the nano filler comprises nano diamond, nano silicon carbide and bio-based nano cellulose, the base material comprises polyimide, polyether-ether-ketone and bio-based polylactic acid, and the functional additive comprises a hindered phenol antioxidant, a nano aluminum hydroxide flame retardant, a nano silicon dioxide reinforcing agent, an ultraviolet light absorber, a carbon nano tube and nano silver particles. Nano-diamond, nano-silicon carbide and bio-based nano-cellulose are adopted as nano-fillers, polyimide, polyether-ether-ketone and bio-based polylactic acid are combined as base materials, and a plurality of functional additives are added, so that the preparation of the high-strength nano-composite stiffening filling master batch is realized; and the problems of poor dispersibility, mechanical property damage, insufficient hardness and poor interface bonding of the traditional filler master batch can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a high-strength nano composite rigidity-enhancing filling masterbatch and a preparation method thereof. Background Art

[0002] The fillers in traditional filler masterbatches are often difficult to disperse evenly in the substrate, resulting in agglomerates or spots in the product, affecting the appearance and performance of the product. In addition, the fillers and additives damage the mechanical properties of the substrate, reduce the tensile strength and impact toughness, and cause the product to have insufficient hardness. The present application can solve the problems of poor dispersibility, damage to mechanical properties, insufficient hardness and poor interface bonding of traditional filler masterbatches.

[0003] The defects of existing filling masterbatch are: 1. Patent document CN103724674B discloses a starch transparent filler masterbatch and a preparation method thereof. The document mainly considers how to solve the problems of high density, poor compatibility, small addition amount and difficult degradation of transparent film filler masterbatch, but does not consider how to solve the problems of poor dispersibility, mechanical property damage, insufficient hardness and poor interface bonding of traditional filler masterbatch; 2. Patent document CN100432138C discloses a filler masterbatch for black plastic and a preparation method thereof. The document mainly considers how to solve the problem that the traditional filler masterbatch needs to be added with both the filler masterbatch and the black masterbatch when used to process black plastic, resulting in increased product cost and decreased performance, but does not consider how to solve the problem of decreased performance caused by agglomeration and uneven dispersion of nanofillers; 3. Patent document CN104497406B discloses a filler masterbatch for transparent film and a preparation method thereof. The document mainly considers how to solve the problem of low content and high cost when barium sulfate is used as a filler in the prior art, but does not consider how to solve the problem of unstable performance caused by poor compatibility between nanofillers and matrix materials; 4. Patent document CN114276694B discloses a filling masterbatch containing FRP and its application. The document mainly considers how to provide a method for recycling FRP in retired / scrapped blades, nacelle covers, fairings and other components of wind turbines, and how to process the recycled FRP into powder for use in plastic filling masterbatch. However, it does not consider how to solve the problems of difficulty in processing the filling masterbatch, low yield rate and performance changes during storage and use. Summary of the invention

[0004] The object of the present invention is to provide a high-strength nano-composite rigidity-enhancing filler masterbatch and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a high-strength nano-composite stiffening filler masterbatch, the raw materials of which include: nano-filler, matrix material and functional additives; The nanofiller includes nanodiamond, nanosilicon carbide and bio-based nanocellulose, with nanodiamond accounting for 16-29 parts, nanosilicon carbide accounting for 21-34 parts and bio-based nanocellulose accounting for 3-6 parts; The matrix material includes polyimide, polyetheretherketone and bio-based polylactic acid, with polyimide accounting for 42-58 parts, polyetheretherketone accounting for 23-41 parts, and bio-based polylactic acid accounting for 11-19 parts; Functional additives include hindered phenol antioxidants, nano-aluminum hydroxide flame retardants, nano-silicon dioxide reinforcing agents, UV absorbers, carbon nanotubes and nano-silver particles; The hindered phenol antioxidant is 3-8 parts, the nano aluminum hydroxide flame retardant is 5-12 parts, the nano silicon dioxide reinforcing agent is 4-9 parts, the ultraviolet absorber is 2-6 parts, the carbon nanotube is 2-4 parts, and the nano silver particles are 0.5-2 parts.

[0006] Preferably, the particle size of nanodiamond is 32-43 nm, and the particle size of nanosilicon carbide is 46-57 nm; The nano-diamond is treated with a silane coupling agent, and the nano-silicon carbide is coated with polydopamine.

[0007] Preferably, the relative molecular mass of polyimide is 65000-950000, and the relative molecular mass of polyetheretherketone is 35000-55000; Polyimide, polyetheretherketone and bio-based polylactic acid are formed into a composite matrix by combining blending and copolymerization.

[0008] Preferably, the bio-based nanocellulose is one or more of cellulose nanowhiskers or cellulose nanofibers; The carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes, and the particle size of the nanosilver particles is 14-34 nm.

[0009] Preferably, a method for preparing a high-strength nano-composite reinforced filler masterbatch comprises the following steps: Step S1, pretreatment and dispersion of nanofillers; Step S2, preparation and coating of matrix material solution; Step S3, forming processing; Step S4, curing and post-processing; Step S5: masterbatch performance testing and packaging and storage.

[0010] Preferably, in step S1, it also includes: Step S11: adding nano-diamond, nano-silicon carbide and bio-based nano-cellulose to an N-methylpyrrolidone solution containing a polyethylene glycol derivative dispersant, respectively, adding 0.5%-2% of polyvinyl pyrrolidone as a stabilizer based on the total mass of the nano-filler, the amount of the polyethylene glycol derivative dispersant added is 3%-8% of the total mass of the nano-filler, and the mass concentration of the nano-filler is 10%-20%; Step S12: subjecting the solution of step S11 to ultrasonic treatment, with an ultrasonic frequency of 22-38 kHz and an ultrasonic time of 35-55 minutes; Step S13: After ultrasonic treatment, auxiliary dispersion is performed in a supercritical carbon dioxide fluid environment, the pressure of the supercritical carbon dioxide is 7.38-10MPa, the temperature is 31.1-35°C, the treatment time is 15-30 minutes, and then high-speed shear dispersion is performed, the high-speed shear speed is 5000-10000rpm, and the shear time is 10-20 minutes.

[0011] Preferably, in step S2, it also includes: Step S21: dissolving polyimide, polyetheretherketone and bio-based polylactic acid in N-methylpyrrolidone solution to form a matrix solution, wherein the mass concentration of the matrix solution is 20%-30%; Step S22: adding the dispersed nanofiller mixed solution to the matrix solution, blending the solution under the protection of inert gas, stirring the solution at a speed of 500-1000rpm, ultrasonic power of 100-200W, and blending the solution for 2-4 hours, then adding a diisocyanate compound as a cross-linking agent for chemical reaction, the addition amount of the diisocyanate compound is 1%-3% of the total mass of the matrix material, the chemical reaction temperature is 60-80°C, and the reaction time is 1-2 hours; Step S23: Finally, hot pressing is performed at 100-150° C. and 5-10 MPa for 1-2 hours, and the nanofiller is combined with the matrix material to form a coating structure.

[0012] Preferably, in step S3, it also includes: Step S31: crushing the coated material into particles; Step S32: The spline is prepared by injection molding process, the injection temperature is 350-400°C, the injection pressure is 80-120MPa, the mold temperature is 150-200°C, and the cooling rate of the mold during the injection molding process is 10-20°C / min.

[0013] Preferably, in step S4, it also includes: Step S41: adopting a staged curing method, first maintaining at a low temperature section of 300-320°C for 1-1.5 hours, then heating to a high temperature section of 330-350°C for final curing for 1-2.5 hours; Step S42: The formed filler masterbatch product may be subjected to plasma surface treatment to introduce carboxyl functional groups on the surface of the masterbatch.

[0014] Preferably, in step S5, it also includes: Step S51: performing performance tests on the prepared filling masterbatch, including tensile strength, flexural strength, impact strength, heat deformation temperature, flame retardancy, electrical conductivity and antibacterial properties; Step S52: The performance-optimized filling masterbatch is packaged with moisture-proof and oxidation-resistant packaging materials. The storage environment includes a temperature of 10-30° C., a humidity of 30%-60%, and avoidance of direct sunlight. The moisture-proof and oxidation-resistant packaging materials are aluminum foil composite bags or metallized plastic film bags.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts nano-diamond, nano-silicon carbide and bio-based nano-cellulose as nano-fillers, combines polyimide, polyetheretherketone and bio-based polylactic acid as matrix materials, and adds a variety of functional additives to achieve the preparation of high-strength nano-composite stiffening filler masterbatch. Compared with the prior art, it can not only significantly improve the rigidity and strength of the filler masterbatch, so that it can withstand greater external forces without deformation or damage, but also maintain good biocompatibility and environmental friendliness. Nano-diamond has ultra-high hardness and good thermal stability, nano-silicon carbide has excellent high temperature resistance and wear resistance, and bio-based nano-cellulose gives the material a certain flexibility and biodegradability. The three work synergistically to comprehensively improve the comprehensive performance of the filler masterbatch, thereby solving the problems of poor dispersibility, mechanical property damage, insufficient hardness and poor interface bonding of traditional filler masterbatch.

[0016] 2. The present invention realizes uniform dispersion of nanofillers in the matrix material through pretreatment and dispersion technology of nanofillers, including the use of polyethylene glycol derivative dispersants, polyvinyl pyrrolidone stabilizers and supercritical carbon dioxide fluid assisted dispersion. The application of this technology not only improves the binding force between nanofillers and matrix materials, but also significantly improves the overall performance of the material. Compared with the prior art, this uniformly dispersed nanofiller can more effectively enhance the mechanical properties of the material and avoid the performance degradation caused by agglomeration and uneven dispersion of nanofillers. Uniformly dispersed nanofillers can form a more stable stress transfer network in the matrix, so that when the material is subjected to external forces such as stretching and bending, the stress can be evenly distributed, thereby significantly improving the mechanical indicators such as tensile strength and bending modulus of the filling masterbatch, thereby improving the reliability and service life of the filling masterbatch, and can be widely used in long-term use scenarios with high requirements for the stability of the performance of the filling masterbatch, so that the problem of performance degradation caused by agglomeration and uneven dispersion of nanofillers can be solved.

[0017] 3. The present invention uses matrix material solution preparation and coating technology to add the dispersed nanofiller mixture into the matrix solution, blend the solution under the protection of inert gas, add a cross-linking agent for chemical reaction, and finally form a coating structure under hot pressing conditions. This technology not only improves the compatibility and bonding between the nanofiller and the matrix material, but also significantly improves the mechanical properties and stability of the filling masterbatch. Compared with the prior art, this coating structure can more effectively prevent the nanofiller from falling off and uneven dispersion. The coating structure allows the nanofiller to be tightly wrapped in the matrix, and can still maintain stable performance in harsh environments such as high temperature and high humidity, effectively improving the durability and reliability of the filling masterbatch, thereby solving the problem of unstable performance caused by poor compatibility between the nanofiller and the matrix material.

[0018] 4. The present invention realizes the preparation and performance optimization of high-strength nano-composite rigid-enhancing filling masterbatch through molding processing, curing and post-processing, as well as performance testing and packaging and storage steps. Compared with the prior art, this preparation process not only improves the processing performance and yield rate of the filling masterbatch, reduces the production cost, but also ensures the stability and reliability of the filling masterbatch during storage and use. In addition, the present invention also adopts technical means such as segmented curing and plasma surface treatment to further improve the mechanical properties and surface properties of the filling masterbatch. Segmented curing can make the internal structure of the filling masterbatch more dense and uniform, and plasma surface treatment improves the activity and hydrophilicity of the surface of the filling masterbatch. These optimization measures enable the high-strength nano-composite rigid-enhancing filling masterbatch of the present invention to maintain excellent performance during processing, storage and use, thereby solving the problems of difficulty in processing the filling masterbatch, low yield rate, and performance changes during storage and use. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Embodiment 1: A high-strength nano-composite stiffening and filling masterbatch, the raw materials include: Nanofiller: 18 parts of nanodiamond, 23 parts of nanosilicon carbide, 4 parts of bio-based nanocellulose; Matrix material: 45 parts of polyimide, 25 parts of polyetheretherketone, 13 parts of bio-based polylactic acid; Functional additives: 4 parts of hindered phenol antioxidant, 6 parts of nano aluminum hydroxide flame retardant, 5 parts of nano silicon dioxide reinforcing agent, 3 parts of ultraviolet absorber, 2.5 parts of carbon nanotubes, 1 part of nano silver particles; A method for preparing a high-strength nano-composite reinforced filler masterbatch comprises the following steps: Step S1, pretreatment and dispersion of nanofillers; In step S1, it also includes: Step S11: adding nano-diamond, nano-silicon carbide and bio-based nano-cellulose to an N-methylpyrrolidone solution containing a polyethylene glycol derivative dispersant, respectively, adding 1% polyvinyl pyrrolidone of the total mass of the nano-filler as a stabilizer, the addition amount of the polyethylene glycol derivative dispersant is 4% of the total mass of the nano-filler, and the mass concentration of the nano-filler is 12%; Step S12: subjecting the solution to ultrasonic treatment, with an ultrasonic frequency of 25 kHz and an ultrasonic time of 40 minutes; Step S13: After ultrasonic treatment, auxiliary dispersion is performed in a supercritical carbon dioxide fluid environment, the pressure of the supercritical carbon dioxide is 8 MPa, the temperature is 32° C., the treatment time is 20 minutes, and then high-speed shear dispersion is performed, the high-speed shear speed is 6000 rpm, and the shear time is 12 minutes.

[0021] Step S2, preparation and coating of matrix material solution; In step S2, it also includes: Step S21: dissolving polyimide, polyetheretherketone and bio-based polylactic acid in N-methylpyrrolidone solution to form a matrix solution, wherein the mass concentration of the matrix solution is 22%; Step S22: adding the dispersed nanofiller mixed solution to the matrix solution, blending the solution under the protection of inert gas, stirring the solution at a speed of 600 rpm, ultrasonic power of 120 W, and blending the solution for 2.5 hours, then adding a diisocyanate compound as a cross-linking agent for chemical reaction, the amount of the diisocyanate compound added is 1.5% of the total mass of the matrix material, the chemical reaction temperature is 65° C., and the reaction time is 1.2 hours; Step S23: Finally, hot pressing treatment is performed at 110° C. and 6 MPa for 1.2 hours, and the nanofiller is combined with the matrix material to form a coating structure.

[0022] Step S3, forming processing; In step S3, it also includes: Step S31: crushing the coated material into particles; Step S32: The sample strip is prepared by injection molding process, the injection temperature is 360°C, the injection pressure is 90 MPa, the mold temperature is 160°C, and the cooling rate of the mold during the injection molding process is 12°C / min.

[0023] Step S4, curing and post-processing; In step S4, it also includes: Step S41: adopting a staged curing method, first maintaining the low temperature section at 305°C for 1.2 hours, then heating to a high temperature section at 335°C for final curing for 1.5 hours; Step S42: performing plasma surface treatment on the formed filled masterbatch product to introduce carboxyl functional groups on the surface of the masterbatch.

[0024] Step S5, masterbatch performance testing and packaging and storage; In step S5, it also includes: Step S51: performing performance tests on the prepared filling masterbatch, including tensile strength, flexural strength, impact strength, heat deformation temperature, flame retardancy, electrical conductivity and antibacterial properties; Step S52: The performance-optimized filling masterbatch is packaged in an aluminum foil composite bag, and the storage environment includes a temperature of 15° C., a humidity of 40%, and avoids direct sunlight.

[0025] Embodiment 2: A high-strength nano-composite stiffening and filling masterbatch, the raw materials include: Nano filler: 20 parts of nano diamond, 26 parts of nano silicon carbide, 5 parts of bio-based nano cellulose; Matrix material: 48 parts of polyimide, 30 parts of polyetheretherketone, 15 parts of bio-based polylactic acid; Functional additives: 5 parts of hindered phenol antioxidant, 8 parts of nano aluminum hydroxide flame retardant, 7 parts of nano silicon dioxide reinforcing agent, 4 parts of ultraviolet absorber, 3 parts of carbon nanotubes, 1.5 parts of nano silver particles; A method for preparing a high-strength nano-composite reinforced filler masterbatch comprises the following steps: Step S1, pretreatment and dispersion of nanofillers; In step S1, it also includes: Step S11: adding nano-diamond, nano-silicon carbide and bio-based nano-cellulose to an N-methylpyrrolidone solution containing a polyethylene glycol derivative dispersant, respectively, adding 1.5% polyvinyl pyrrolidone of the total mass of the nano-filler as a stabilizer, the addition amount of the polyethylene glycol derivative dispersant is 6% of the total mass of the nano-filler, and the mass concentration of the nano-filler is 15%; Step S12: subjecting the solution to ultrasonic treatment, with an ultrasonic frequency of 30 kHz and an ultrasonic time of 45 minutes; Step S13: After ultrasonic treatment, auxiliary dispersion is performed in a supercritical carbon dioxide fluid environment, the pressure of the supercritical carbon dioxide is 9 MPa, the temperature is 33° C., the treatment time is 25 minutes, and then high-speed shear dispersion is performed, the high-speed shear speed is 8000 rpm, and the shear time is 15 minutes.

[0026] Step S2, preparation and coating of matrix material solution; In step S2, it also includes: Step S21: dissolving polyimide, polyetheretherketone and bio-based polylactic acid in N-methylpyrrolidone solution to form a matrix solution, wherein the mass concentration of the matrix solution is 25%; Step S22: adding the dispersed nanofiller mixed solution to the matrix solution, blending the solution under the protection of inert gas, stirring the solution at a speed of 800 rpm, ultrasonic power of 150 W, and blending the solution for 3 hours, then adding a diisocyanate compound as a cross-linking agent for chemical reaction, the addition amount of the diisocyanate compound is 2% of the total mass of the matrix material, the chemical reaction temperature is 70° C., and the reaction time is 1.5 hours; Step S23: Finally, hot pressing treatment is performed at 130° C. and 8 MPa for 1.5 hours, and the nanofiller is combined with the matrix material to form a coating structure.

[0027] Step S3, forming processing; In step S3, it also includes: Step S31: crushing the coated material into particles; Step S32: The sample strip is prepared by injection molding process, the injection temperature is 380° C., the injection pressure is 100 MPa, the mold temperature is 180° C., and the cooling rate of the mold during the injection molding process is 15° C. / min.

[0028] Step S4, curing and post-processing; In step S4, it also includes: Step S41: adopting a staged curing method, first maintaining the low temperature section at 310°C for 1.3 hours, then heating to a high temperature section at 340°C for final curing for 2 hours; Step S42: performing plasma surface treatment on the formed filled masterbatch product to introduce carboxyl functional groups on the surface of the masterbatch.

[0029] Step S5, masterbatch performance testing and packaging and storage; In step S5, it also includes: Step S51: performing performance tests on the prepared filling masterbatch, including tensile strength, flexural strength, impact strength, heat deformation temperature, flame retardancy, electrical conductivity and antibacterial properties; Step S52: The performance-optimized filling masterbatch is packaged in a metallized plastic film bag, and the storage environment includes a temperature of 20° C., a humidity of 50%, and avoids direct sunlight.

[0030] Embodiment three: A high-strength nano-composite stiffening and filling masterbatch, the raw materials include: Nano filler: 25 parts of nano diamond, 30 parts of nano silicon carbide, 5.5 parts of bio-based nano cellulose; Matrix material: 52 parts of polyimide, 35 parts of polyetheretherketone, 17 parts of bio-based polylactic acid; Functional additives: 6 parts of hindered phenol antioxidant, 10 parts of nano aluminum hydroxide flame retardant, 8 parts of nano silicon dioxide reinforcing agent, 5 parts of ultraviolet absorber, 3.5 parts of carbon nanotubes, 1.8 parts of nano silver particles; A method for preparing a high-strength nano-composite reinforced filler masterbatch comprises the following steps: Step S1, pretreatment and dispersion of nanofillers; In step S1, it also includes: Step S11: adding nano-diamond, nano-silicon carbide and bio-based nano-cellulose to an N-methylpyrrolidone solution containing a polyethylene glycol derivative dispersant, respectively, adding 1.8% polyvinyl pyrrolidone of the total mass of the nano-filler as a stabilizer, the addition amount of the polyethylene glycol derivative dispersant is 7% of the total mass of the nano-filler, and the mass concentration of the nano-filler is 18%; Step S12: subjecting the solution to ultrasonic treatment, with an ultrasonic frequency of 35 kHz and an ultrasonic time of 50 minutes; Step S13: After ultrasonic treatment, auxiliary dispersion is performed in a supercritical carbon dioxide fluid environment, the pressure of the supercritical carbon dioxide is 9.5 MPa, the temperature is 34° C., the treatment time is 28 minutes, and then high-speed shear dispersion is performed, the high-speed shear speed is 9000 rpm, and the shear time is 18 minutes.

[0031] Step S2, preparation and coating of matrix material solution; In step S2, it also includes: Step S21: dissolving polyimide, polyetheretherketone and bio-based polylactic acid in N-methylpyrrolidone solution to form a matrix solution, wherein the mass concentration of the matrix solution is 28%; Step S22: adding the dispersed nanofiller mixed solution to the matrix solution, blending the solution under the protection of inert gas, stirring the solution at a speed of 900 rpm, ultrasonic power of 180 W, and blending the solution for 3.5 hours, then adding a diisocyanate compound as a cross-linking agent for chemical reaction, the amount of the diisocyanate compound added is 2.5% of the total mass of the matrix material, the chemical reaction temperature is 75° C., and the reaction time is 1.8 hours; Step S23: Finally, hot pressing treatment is performed at 140° C. and 9 MPa for 1.8 hours, and the nanofiller is combined with the matrix material to form a coating structure.

[0032] Step S3, forming processing; In step S3, it also includes: Step S31: crushing the coated material into particles; Step S32: The sample strip is prepared by injection molding process, the injection temperature is 390° C., the injection pressure is 110 MPa, the mold temperature is 190° C., and the cooling rate of the mold during the injection molding process is 18° C. / min.

[0033] Step S4, curing and post-processing; In step S4, it also includes: Step S41: adopting a staged curing method, first maintaining the low temperature section at 315°C for 1.4 hours, then heating to a high temperature section at 345°C for final curing for 2.2 hours; Step S42: performing plasma surface treatment on the formed filled masterbatch product to introduce carboxyl functional groups on the surface of the masterbatch.

[0034] Step S5, masterbatch performance testing and packaging and storage; In step S5, it also includes: Step S51: performing performance tests on the prepared filling masterbatch, including tensile strength, flexural strength, impact strength, heat deformation temperature, flame retardancy, electrical conductivity and antibacterial properties; Step S52: The performance-optimized filling masterbatch is packaged in an aluminum foil composite bag, and the storage environment includes a temperature of 25° C., a humidity of 55%, and avoids direct sunlight.

[0035] Embodiment 4: A method for preparing a high-strength nano-composite reinforced filling masterbatch. The filling masterbatches prepared in Example 1, Example 2 and Example 3 are subjected to performance tests, including tensile strength, flexural strength, impact strength, heat deformation temperature, flame retardancy, electrical conductivity and antibacterial properties. The performance test results are as follows:

[0036] The performance test results show that: As the raw material ratios and preparation process parameters in each example change, the tensile strength shows an upward trend. The tensile strength of Example 1 is 120MPa, which is increased to 150MPa in Example 2, and further increased to 180MPa in Example 3, indicating that the continuous adjustment of the amount of nanofiller, matrix material and various parameters in the preparation process has a positive effect on the tensile strength of the final filling masterbatch, making it continuously enhanced. Similarly, the bending strength also gradually increases from 180MPa in Example 1, to 220MPa in Example 2, and then to 250MPa in Example 3, reflecting that the different ratios and process improvements adopted are helpful to improve the strength performance of the filling masterbatch products when subjected to bending forces.

[0037] The impact strength values ​​show a downward trend, with 8 kJ / m² for Example 1, 6 kJ / m² for Example 2, and 5 kJ / m² for Example 3. This means that with the improvement of tensile strength and bending strength, the ability of the filled masterbatch product to resist impact is weakened under the current material ratio and preparation process adjustment, because the change in the internal structure of the material and other factors make its performance in dealing with instantaneous impact not as good as before.

[0038] The heat deformation temperature increases continuously from 250°C in Example 1 to 280°C in Example 2 and then to 300°C in Example 3. This indicates that through the material selection and process optimization in each embodiment, the filled masterbatch product can maintain its shape and stable performance in a higher temperature environment, and the thermal stability is significantly improved, so that it can be used in scenes with higher temperature requirements.

[0039] The flame retardant performance is improved from V-1 level in Example 1 to V-0 level in Example 2 and Example 3. This shows that with the adjustment of material composition and preparation process, the flame retardant effect of the filled masterbatch product has been significantly enhanced, the performance in fire safety is more outstanding, and it can better meet some applications with higher flame retardant requirements.

[0040] The electrical conductivity is manifested in a gradual decrease in resistivity, with the resistivity of Example 1 being 1.2×10⁻³Ω・m, that of Example 2 being 0.8×10⁻³Ω・m, and that of Example 3 being 0.5×10⁻³Ω・m. This indicates that in the process of continuously optimizing the material ratio and the preparation process, the electrical conductivity of the filled masterbatch product is gradually enhanced, which is a favorable improvement for some application scenarios that require certain electrical conductivity.

[0041] The antibacterial rate of the antibacterial performance gradually increased from 90% in Example 1 to 95% in Example 2 and then to 98% in Example 3. This reflects that the changes in the material combination and preparation process used are helpful to improve the ability of the filling masterbatch product to inhibit bacterial growth, so that it may have better application prospects in fields requiring antibacterial properties such as medical care, food packaging, etc.

[0042] Example 3 performs relatively well in terms of tensile strength, flexural strength and electrical conductivity, which is attributed to its higher content of nano-diamond, nano-silicon carbide and carbon nanotube components. These fillers can effectively enhance the mechanical properties and electrical conductivity of the material. However, its impact strength is relatively low, and the toughness of the material decreases due to the increase of high-strength fillers.

[0043] The performance of Example 2 is relatively balanced, with tensile strength, flexural strength, heat deformation temperature and antibacterial properties all at an upper-middle level. The impact strength is better than that of Example 3, and it has advantages in some application scenarios that have high requirements for comprehensive performance and certain requirements for impact performance.

[0044] The performance of Example 1 is relatively weak, but it may have certain application value in some fields that are more cost-sensitive and have low performance requirements, including ordinary plastic modification. In terms of flame retardancy, Examples 2 and 3 both reach V-0 level, thanks to the higher content of nano aluminum hydroxide flame retardant and the flame retardant properties of the base material itself.

[0045] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A high-strength nano-composite stiffening filler masterbatch, characterized in that: Raw materials include: Nanofillers, matrix materials and functional additives; The nanofiller includes nanodiamond, nanosilicon carbide and bio-based nanocellulose, with nanodiamond accounting for 16-29 parts, nanosilicon carbide accounting for 21-34 parts and bio-based nanocellulose accounting for 3-6 parts; The matrix material includes polyimide, polyetheretherketone and bio-based polylactic acid, with polyimide accounting for 42-58 parts, polyetheretherketone accounting for 23-41 parts, and bio-based polylactic acid accounting for 11-19 parts; Functional additives include hindered phenol antioxidants, nano-aluminum hydroxide flame retardants, nano-silicon dioxide reinforcing agents, UV absorbers, carbon nanotubes and nano-silver particles; The hindered phenol antioxidant is 3-8 parts, the nano aluminum hydroxide flame retardant is 5-12 parts, the nano silicon dioxide reinforcing agent is 4-9 parts, the ultraviolet absorber is 2-6 parts, the carbon nanotube is 2-4 parts, and the nano silver particles are 0.5-2 parts.

2. The high-strength nano-composite stiffening filler masterbatch according to claim 1, characterized in that: The particle size of nanodiamond is 32-43nm, and the particle size of nanosilicon carbide is 46-57nm; The nano-diamond is treated with a silane coupling agent, and the nano-silicon carbide is coated with polydopamine.

3. The high-strength nano-composite stiffening filler masterbatch according to claim 1, characterized in that: The relative molecular mass of polyimide is 65000-950000, and the relative molecular mass of polyetheretherketone is 35000-55000; Polyimide, polyetheretherketone and bio-based polylactic acid are formed into a composite matrix by combining blending and copolymerization.

4. The high-strength nano-composite stiffening filler masterbatch according to claim 1, characterized in that: The bio-based nanocellulose is one or more of cellulose nanowhiskers or cellulose nanofibers; The carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes, and the particle size of the nanosilver particles is 14-34 nm.

5. A method for preparing a high-strength nano-composite reinforced filler masterbatch, characterized in that: The following steps are involved: Step S1, pretreatment and dispersion of nanofillers; Step S2, preparation and coating of matrix material solution; Step S3, forming processing; Step S4, curing and post-processing; Step S5: masterbatch performance testing and packaging and storage.

6. The method for preparing a high-strength nano-composite rigidity-enhancing filler masterbatch according to claim 5, characterized in that: In step S1, it also includes: Step S11: adding nano-diamond, nano-silicon carbide and bio-based nano-cellulose to an N-methylpyrrolidone solution containing a polyethylene glycol derivative dispersant, respectively, adding 0.5%-2% of polyvinyl pyrrolidone as a stabilizer based on the total mass of the nano-filler, the amount of the polyethylene glycol derivative dispersant added is 3%-8% of the total mass of the nano-filler, and the mass concentration of the nano-filler is 10%-20%; Step S12: subjecting the solution of step S11 to ultrasonic treatment, with an ultrasonic frequency of 22-38 kHz and an ultrasonic time of 35-55 minutes; Step S13: After ultrasonic treatment, auxiliary dispersion is performed in a supercritical carbon dioxide fluid environment, the pressure of the supercritical carbon dioxide is 7.38-10MPa, the temperature is 31.1-35°C, the treatment time is 15-30 minutes, and then high-speed shear dispersion is performed, the high-speed shear speed is 5000-10000rpm, and the shear time is 10-20 minutes.

7. The method for preparing a high-strength nano-composite rigidity-enhancing filler masterbatch according to claim 5, characterized in that: In step S2, it also includes: Step S21: dissolving polyimide, polyetheretherketone and bio-based polylactic acid in N-methylpyrrolidone solution to form a matrix solution, wherein the mass concentration of the matrix solution is 20%-30%; Step S22: adding the dispersed nanofiller mixed solution to the matrix solution, blending the solution under the protection of inert gas, stirring the solution at a speed of 500-1000rpm, ultrasonic power of 100-200W, and blending the solution for 2-4 hours, then adding a diisocyanate compound as a cross-linking agent for chemical reaction, the amount of the diisocyanate compound added is 1%-3% of the total mass of the matrix material, the chemical reaction temperature is 60-80°C, and the reaction time is 1-2 hours; Step S23: Finally, hot pressing is performed at 100-150° C. and 5-10 MPa for 1-2 hours, and the nanofiller is combined with the matrix material to form a coating structure.

8. The method for preparing a high-strength nano-composite rigidity-enhancing filler masterbatch according to claim 5, characterized in that: In step S3, it also includes: Step S31: crushing the coated material into particles; Step S32: The spline is prepared by injection molding process, the injection temperature is 350-400°C, the injection pressure is 80-120MPa, the mold temperature is 150-200°C, and the cooling rate of the mold during the injection molding process is 10-20°C / min.

9. The method for preparing a high-strength nano-composite rigidity-enhancing filler masterbatch according to claim 5, characterized in that: In step S4, it also includes: Step S41: adopting a staged curing method, first maintaining at a low temperature section of 300-320°C for 1-1.5 hours, then heating to a high temperature section of 330-350°C for final curing for 1-2.5 hours; Step S42: The formed filler masterbatch product may be subjected to plasma surface treatment to introduce carboxyl functional groups on the surface of the masterbatch.

10. The method for preparing a high-strength nano-composite rigidity-enhancing filler masterbatch according to claim 5, characterized in that: In step S5, it also includes: Step S51: performing performance tests on the prepared filling masterbatch, including tensile strength, flexural strength, impact strength, heat deformation temperature, flame retardancy, electrical conductivity and antibacterial properties; Step S52: The performance-optimized filling masterbatch is packaged with moisture-proof and oxidation-resistant packaging materials. The storage environment includes a temperature of 10-30° C., a humidity of 30%-60%, and avoidance of direct sunlight. The moisture-proof and oxidation-resistant packaging materials are aluminum foil composite bags or metallized plastic film bags.

Citation Information

Patent Citations

  • Mother filler of black plastic and its preparing process

    CN100432138C

  • A transparent starch filler masterbatch and its preparation method

    CN103724674B

  • A kind of filling masterbatch for transparent film and preparation method thereof

    CN104497406B

  • A filler masterbatch containing fiberglass and its application

    CN114276694B

Cited By

  • Nano modified polyformaldehyde plastic particle

    CN120484433A

  • Nanomodified polyoxymethylene plastic particles

    CN120484433B

  • Cement strength synergist and preparation method thereof

    CN121202476A